2016
DOI: 10.1186/s12889-016-2928-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits and negative consequences of alcohol consumption in women living with HIV: a qualitative study

Abstract: BackgroundWomen living with HIV have increased prevalence of medical and psychological comorbidities that could be adversely affected by alcohol consumption. Little is known about their unique motivations for drinking or perceptions of HIV-related consequences. In preparation for an alcohol intervention study, we sought to better understand reasons for drinking and perceived consequences of alcohol consumption among a sample of women living with HIV.MethodsFour focus groups, with a total of 24 adult women (96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Initially, we expected marijuana use to be associated with pain as chronic pain is one of the leading reasons for starting medical marijuana. 40 Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLHIV may engage in risky drinking, in order to manage physical pain. 41 A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLHIV.…”
Section: Substance Usementioning
confidence: 82%
“…Initially, we expected marijuana use to be associated with pain as chronic pain is one of the leading reasons for starting medical marijuana. 40 Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLHIV may engage in risky drinking, in order to manage physical pain. 41 A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLHIV.…”
Section: Substance Usementioning
confidence: 82%
“…37 Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLWH may engage in risky drinking, in order to manage physical pain. 38 A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLWH. 39 However, studies investigating the associations between marijuana use and pain have reported reductions in pain severity among the general population.…”
Section: Substance Usementioning
confidence: 85%
“…Initially, we expected marijuana use to be associated with pain as chronic pain is one of the leading reasons for starting medical marijuana [40]. Similarly, we thought alcohol may be associated with pain as a recently published qualitative study, Cook et al concluded that PLHIV may engage in risky drinking, in order to manage physical pain [41]. A similar study by Merlin et al also noted marijuana use was not statistically associated with reductions in pain among PLHIV [42].…”
Section: Substance Usementioning
confidence: 87%